PENGARUH MODEL PEMBELAJARAN EXAMPLE NON EXAMPLE DENGAN MEDIA FLASHCARD TERHADAP KEMAMPUAN PEMAHAMAN KONSEP IPA PESERTA DIDIK SEKOLAH DASAR - Fiksi Kirana Sarizaen; Fitri Nuraeni; Tiara Yogiarni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Concept understanding ability is a foundation that can help students in the learning process at school, especially for elementary school students in science subjects. Through a good understanding of science, students will be able to solve problems that occur in their environment. However, the ability to understand science concepts in elementary school students is still known to be an urgency that needs to be addressed immediately. Therefore, the objectives of this study include to determine how the effect of the example non example learning model with flashcard media on the ability to understand science concepts and to find out how the difference in improving the ability to understand science concepts in students through the example non example learning model with flashcard media and in students through the think pair share learning model. This research is a quasi-experimental research type nonequivalent control group design with a sample of 26 participants in the experimental class and 24 participants in the control class. The results showed the simple linear regression test results of 26.8% and the n-gain test results in the experimental class of 0.4109 and in the control class of 0.3205. Based on these results, it can be concluded that the example non example learning model with flashcard media has a positive effect on the ability to understand science concepts of elementary school students and this model provides a greater increase in the ability to understand science concepts compared to the think pair share learning model. Thus, the example non example learning model with flashcard media can be an alternative learning strategy in building the ability to understand the science concepts of students in elementary schools.